(untitled) (Bangladesh Journal of Child Health, 2021)
Hematohidrosis (bloody sweat) is a very rare clinical entity characterized by recurrent, spontaneous, self-limited episodes of blood oozing from intact skin or mucosa. A 12-year-old girl presented to our hospital with a history of repeated episodes of oozing of blood from different parts of the body like eyes, ear lobules, nose & navel. She also had history of episodes of hematemesis and haematuria. During examination, bleeding disappeared as soon as it was mopped leaving behind no sign of trauma. Most of these bleeding episodes occurred after stress. Her laboratory evaluation showed; bleeding time, clotting time and prothrombin time were normal. On the basis of clinical presentation and normal investigation, she was diagnosed as a case of hematohidrosis. We treated her with non-specific beta-blocker (propranolol). In spite of the rarity of hematohidrosis, it should be considered as a differential diagnosis of bleeding episodes in patients with normal physical and laboratory investigations. BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 45-47